El efecto pandémico y su influencia en el proceso de enseñanza - aprendizaje en la unidad educativa Adolfo María Astudillo, Babahoyo - Olaya Rodríguez, Leslie Alison (2021)
The Covid-19 (Coronavirus) epidemic is a threat to education around the world significant results: 1) School closings almost everywhere in the world 2) Economic recession as a consequence of the measures taken to combat the epidemic. Unless significant efforts are made to counter its effects, school closures will lead to a loss of learning, an increase in early school leaving (also known as dropout rates) and greater inequality. The economic crisis affecting households is exacerbating the damage, as it leads to a decline in the supply and demand for education. Together these two effects have long-term costs to human capital and well-being. However, if countries respond quickly to the learning support they are in progress, they can reduce the damage and even make recovery a new option. Public policy responses to this can be summarized in three overlapping phases: addressing the epidemic, addressing continuity issues, and improving and accelerating learning. One of the most relevant results that we can emphasize is that it was possible to define that virtual tools oriented to education are of vital importance in a context of the pandemic and the decision to close educational institutions causing the "blackout of presence", to facilitate the learning process because it provides us with a new and innovative platform for the development of teaching - learning.